Pemanfaatan Media Sosial Instagram Untuk Digital Marketing Pada UMKM Bakso Dan Es Campur “Family” Di Kota Blitar - Gading Wijaya, Salsa Febiola; Faulia Rahma, Riska; Bahrul Ulum, Krisna; Setyo Budiwitjaksono, Gideon; Marthina Rosyanti, Daisy; Abuzar Zuhri, M. Fernanda (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
The advancement of technology has a significant impact on human existence, and one example of this is information technology, which offers a variety of advantages to the process of creating a business. The information technology in question is known as digital marketing, and its primary purpose is to promote the dissemination of commercial items through various online media, including social media platforms like Instagram. This service takes a comprehensive approach by way of the socialisation component of the intense approach method. According to the findings of this service, there are a number of promotional activities that are carried out by Bakso & Es Campur "Family" business players. One of these activities is the utilisation of the social media platform Instagram. Businesses who sell Bakso & Es Campur "Family" may find it simpler to engage in extensive marketing endeavours if they make use of the numerous tools that can be utilised on Instagram. Some of these capabilities include Instagram feeds, Instagram stories, and Instagram Ads. In this scenario, the efficacy of promotion is also examined in order to reach the target market. The Return on Investment formula is utilised in order to gain an understanding of the impact that investment plays. Social Media, Instagram, Digital Marketing